2021
DOI: 10.3171/2019.12.jns192584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of case volume and comprehensive stroke center capabilities on patient outcomes of clipping and coiling for subarachnoid hemorrhage

Abstract: OBJECTIVEImproved outcomes in patients with subarachnoid hemorrhage (SAH) treated at high-volume centers have been reported. The authors sought to examine whether hospital case volume and comprehensive stroke center (CSC) capabilities affect outcomes in patients treated with clipping or coiling for SAH.METHODSThe authors conducted a nationwide retrospective cohort study in 27,490 SAH patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Relevance and implication of this study Our previous study showed that better outcomes of patients directly transported who receive clipping, but not coiling, may be achieved in hospitals with the highest baseline (>19 points) CSC capabilities (vs lowest: 6-13). 19 In this study, an increased use of coiling, not clipping, was associated with the preceding increase of the CSC capabilities, which was not associated with in-hospital outcomes after clipping. This is in marked contrast to the positive effect of the preceding increase of the CSC capabilities on better outcomes of rt-PA infusion and mechanical thrombectomy in patients with acute ischemic stroke (AIS) in our previous study.…”
Section: Open Accessmentioning
confidence: 49%
See 1 more Smart Citation
“…Relevance and implication of this study Our previous study showed that better outcomes of patients directly transported who receive clipping, but not coiling, may be achieved in hospitals with the highest baseline (>19 points) CSC capabilities (vs lowest: 6-13). 19 In this study, an increased use of coiling, not clipping, was associated with the preceding increase of the CSC capabilities, which was not associated with in-hospital outcomes after clipping. This is in marked contrast to the positive effect of the preceding increase of the CSC capabilities on better outcomes of rt-PA infusion and mechanical thrombectomy in patients with acute ischemic stroke (AIS) in our previous study.…”
Section: Open Accessmentioning
confidence: 49%
“…[16][17][18] Our recent study showed that CSC capabilities were significantly associated with lower in-hospital mortality in clipped, but not coiled, patients with SAH, suggesting that in the modern endovascular era, better outcomes of clipping may be achieved in facilities with high CSC capabilities. 19 Notably, we found a significant improvement in the CSC capabilities between 2010 and 2018, which was mainly related to the availability of endovascular treatment and multidisciplinary care. 20 Taken together, these studies raise a question regarding the effect of temporal changes in CSC capabilities on the overall clinical outcomes of patients with SAH and the therapeutic choices and outcomes of patients who have undergone clipping and coiling in the modern endovascular era.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 72%
“…Therein, we demonstrated that hospitals with higher (vs. lower) CSC capabilities were more likely to have lower in-hospital mortality among patients with AIS and to provide timely rt-PA infusion and MT on a 24-h basis 2 , 7 . Although the CSC score comprises heterogeneous items of stroke care expertise, it reflects the joint effort of multiple healthcare professionals to manage emergencies 7 , 9 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Participation of hospitals in the J-ASPECT study was voluntary, and the study was performed in collaboration with the Japan Neurosurgical Society (JNS) and Japan Stroke Society (JSS) 2 , 7 , 8 , 11 . This study consisted of two projects: (1) an institutional survey to assess the CSC capabilities of the hospitals (Table 1 ) 9 , 12 and (2) a retrospective cohort study using the nationwide Diagnosis Procedure Combination (DPC) inpatient database 2 , 7 , 8 , 11 . Briefly, the DPC is a mixed-case classification system linked with a lump-sum payment system that was launched in 2002 by the Ministry of Health, Labor, and Welfare of Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence shows that high-volume cerebrovascular centers of excellence with both microsurgery and endovascular surgery specialists produce superior patient outcomes. 1,[8][9][10] Medical bills are the leading cause of personal bankruptcy in the United States. 11 Healthcare costs contribute to approximately 18% of the gross domestic product ($3.6 trillion or $11 172/ person).…”
mentioning
confidence: 99%